"Лапки" як графічний маркер інтекстової інформації в листах Лесі Українки - Приходько (Андрощук), Наталія Степанівна; Prykhodko (Androshchuk), Nataliia S. (My University, 2014)
У статті розглянуто функції візуально-графічного оформлення писемного тексту та особливості його сприйняття адресатом; з’ясовано функції лапок в епістолярних текстах Лесі Українки; проаналізовано різновиди цитувань та способи їх актуалізації.

The article deals with recipient’s perception peculiarities of written text and functions of its visual graphic design; ut is defined the function of quotation marks in Lesia Ukrainka’s epistolary texts; it is analyzed the types of citing and methods of its actualization.
"Quotation marks" as graphical marker of in-text information in Lesia Ukrainka’s letters
Keywords: параграфеміка; синграфеміка; супраграфеміка; топографеміка; епістолярний текст; лист; цитація; лапки; Леся Українка; para-graphemic; syn-graphemic; super-graphemic; topo-graphemic; epistolary text; letter; citing; quotation marks; Lesia Ukrainka